Regulation in a Multisectored Financial Services Industry: An Exploratory Essay - Howell E. Jackson (Washington University Law Quarterly, 1999)
This Article reviews differences in regulatory structure across sectors of the financial services industry in the United States and then explores the difficulties these differences pose to our current system of regulation and also to proposals for financial modernization.
Keywords: Financial services industry; Banking law; Deregulation; Financial institutions; Financial services; Securities law